Living with mental illness in a globalised world : combating stigma and barriers to healthcare - Ikwuka, Ugo (New York, NY : Routledge, 2021)
"Living with Mental Illness in a Globalised World systematically examines the manifold contributions to the burdens of living with mental illness in a developing and globalized world. It explores the stigma of mental illness, the burden of which compares to the symptoms of and is sometimes considered more disabling than the illness itself. The book starts by reviewing the socio-psychological and cultural processes that contribute to stigma and providing evidence-based interventions to combat it. Chapters critically investigate the ideological and instrumental barriers to mental health care and establish that determining the conceptualizations of mental illness helps to unravel the reasons for the underutilization of mental health services. A compelling case is made for a complementary health care model and bottom-up approach that is sensitive to the spiritual and cultural needs of the people. The text's specific examination of mental health care in African countries makes it a timely piece for assisting mental health professionals in understanding the inequities in care that Black Asian and Minority Ethnic groups face and how to improve mental health care and delivery to these groups"--
OCLC-licensed vendor bibliographic record.
Keywords: Mental illness -- Social aspects; Mentally ill -- Public opinion; Stigma (Social psychology); MEDICAL / Psychiatry / General